DISKRITISASI KONTROLER PI PADA PULSE WIDTH MODULATION (PWM) RECTIFIER TIGA FASA - Gasa Gradianto; Tri Nurwati; Bambang Siswojo (Jurnal Mahasiswa TEUB, 2023)
Rectifiers are increasingly being used in various applications such as power supplies for microelectronics, household electrical equipment, battery charging, power conversion in high-voltage direct current (HVDC) transmission systems, and so on. Conventional rectifiers typically use diodes, which are uncontrolled rectifiers that have a disadvantage of producing inflexible output voltage since the output voltage cannot be regulated. Therefore, there is a need for controlled rectifiers, namely three-phase PWM rectifiers, which convert AC voltage into DC voltage with higher output voltage than the input voltage, and the output voltage can be adjusted according to specific requirements. This research discusses the comparison of PI controller design in the sdomain and z-domain with pulse width modulation (PWM) three-phase rectifier as the plant to be controlled.